Ethnobotanical Study of Tumpek Wariga Tradition in Hindu Community of Jagaraga Village, West Lombok Regency - Ni Putu Xena Tantowi; Kurniasih Sukenti; Tri Mulyaningsih (Jurnal Biologi Tropis, 2022)
The Hindu community in Jagaraga Village, West Lombok Regency is a local community whose life is closely related to the use of plants in daily life, including using plants in traditional rituals. Jagaraga Village has areas surrounded by rice fields and farms, therefore the Hindu community in Jagaraga Village performs the Tumpek Wariga traditional ceremony. Tumpek Wariga is held as a form of gratitude for the plants and also as a form of request to the plants to produce a good harvest. This ceremony is carried out 25 days before the Galungan ceremony. This study aims to explore the ethnobotanical aspects of the plants used in the Tumpek Wariga ceremony. The research was conducted in 5 hamlets of the Hindu community of Jagaraga Village, namely Tambang Eleh Hamlet, Lamper Hamlet, Karang Lamper Hamlet, West Jagaraga Hamlet and East Jagaraga Hamlet. All qualitative and quantitative data were analyzed descriptively based on the results of observations, interviews, calculations of Reported Use (RU) and the Index of Cultural Significance (ICS). Data collection in the field is done by observation, interviews, and documentation. The selection of sources using purposive sampling and snowball sampling methods. Based on the results obtained, 59 species of plants belong to 50 generas and 36 families are used in Tumpek Wariga ceremony in the Hindu community of Jagaraga Village, West Lombok Regency. These plants are used as food, other food ingredients such as spices, secondary materials, offerings and ritual equipments.